Pendidikan Budaya dan Budaya Pendidikan - Donatus, Sermada Kelen (Perspektif, 2013)
The Title "Pendidikan Budaya dan Budaya Pendidikan" (Formation of the Cul- ture and Culture of the Formation) contains two concepts which are different from each other. Formation of the culture is dealing with the formation touch- ing the culture. The formation is emphasizing the process of creating the guidelines to develop and to put forward the culture. It involves the process of knowing, cultivating and of developing the essence of the culture. Culture of the formation is the practice of the formation. It means the whole activi- ties that include the styles, the behaviours, the attitude and the way of life, the instruments, the practical concepts, the administration and the manage- ment of the education, the ideology and the philosophy of the education. In other words, culture of the formation is dealing with the question of how a formation or education should be done. The author has an effort to elaborate the two concepts in the different meaning, and at the end of this article, the author would like to apply these two different concepts to the Indonesian context nowadays.